Between Art/Education and life: reconstructing forgotten memories (Revista Apotheke, 2024)
The present article presents processes from the project “What is your forgotten memory?”, which aims to stimulate the individual’s artistic practice based on his experiences, which are surrounded by forgotten memories, but that are remembered through visual objects kept by family members. Sending letters to different recipients was the method adopted so that art could circulate outside the studio, reaching individuals who often have no direct contact with Visual Arts. In this experiment, we use memory concepts from Bosi (2006) and Chaui (2009) to send a letter to the recipients who participated in the project. From the letters sent, which instigate the search for a forgotten memory and consequently the artistic production of the recipients, we sought to develop the self-expression of individuals, proposing an answer to the question “what is your forgotten memory?” In this sense, I interpret the power of this research reverted in the experiences carried out in creative processes and products created, developing in a collective way the concept of memory and tangenting possibilities of Contemporary Art in my formation as a teacher/artist/researcher.
Keywords: memory; art/education; visual arts; contemporary art